Refleksi Kegagalan Salomo Sebagai Pembelajaran Pemimpin Masa Kini, Berdasarkan 1 Raja-Raja 11:1-8; 40; 12:1-5: Solomon; Jeroboam; Rehoboam; Failure; Wisdom - Pattinaja, Aska (Sekolah Tinggi Teologi Excelsius, 2025)
Solomon, was a very wise king on this earth, because of God's grace to him. But ironically, Solomon ended his reign by leaving behind a very wrong and fatal decision, namely the division of the kingdom of Israel 1 Kings 11:1-8; 40; 12:1-5. It turned out that free will, which was not properly controlled, had defeated his wisdom. There is a research gap in discussing Solomon's failure. Previous studies focused more on Solomon's wisdom and success. For this reason, the purpose of this study is to explore Solomon's failures and mistakes, at the end of his life, so that they become important lessons for today's leaders. Based on the method of literature study and exposition, several important things were found from the story of Solomon's failure, namely: first, the comfort of being a powerful and rich king; second, ignoring wisdom leads to wrong decisions; third, making the wrong decision in choosing a life partner has fatal consequences. The results of this study are very important, and serve as a reference for leaders who are entrusted with power and responsibility by God to always walk on the truth.